New Perspectives of the Communist Party of Vietnam on Religion and Some Issues Raised for Religious Policies in Vietnam Today - Than Hoa, Le; Le Dinh Troung (MultiTech Publisher, 2024)
Vietnam is a country with diverse forms of beliefs and religions coexisting and developing. Nowadays, religions have made significant contributions to the construction of national solidarity, actively participating in and effectively contributing to activities in healthcare, education, and charity, and positively contributing to the overall development of the country. However, alongside the positive activities of religions, there are still many instances in society where some individuals exploit beliefs and religions for superstitious and divisive purposes, deceiving the people, and even undermining national solidarity. This article aims to explore the new viewpoint of the Communist Party of Vietnam on religion, evaluate the current situation of implementing religious policies, and propose some recommendations to improve religious policies according to the viewpoint of the 13th National Party Congress of the Communist Party of Vietnam in Vietnam today.